ChemInform Abstract: Synthesis, Crystal Structure, and Properties of an Interesting Elliptical Vanadoborate Housing Crystal: [Ni(en)2]6 [(VO)12O6B18O39(OH)3] ·5H2O. Issue 10 (March 2015) - Jiang, Xiangzhan; Dong, Xiaoyu; Pan, Shilie; Han, Jian; Yang, Yun; Zhang, Fangyuan; Yu, Hongwei
Abstract The new title compound is hydrothermally synthesized by reaction of Ni(OAc)2, V2O5, H3BO3, and en in H2O (autoclave, 200 °C, 3 d, 92% yield).